Assessment of Risk Factors for Thyroid Cancer Patients at Tishreen University Hospital - علوش علي; عيسى يونس (Latakia University Journal -Medical Sciences Series, 2020)
Background and Objectives: Thyroid cancer is the most common endocrine malignancy. Several risk factors were found to play a role in thyroid cancer. The aim of the study was to identify risk factors for thyroid cancer in Lattakia and to assess the relationship between some types of food and thyroid cancer. Materials and Methods: The Non-experimental Quantitative design (a Case – Control approach) was used in this study. The study was conducted at Tishreen University Hospital, Lattakia, Syria. The period from June 2016 to June 2019. A formal consent was taken from all participants (case group and control group) in questionnaire. A nonprobability purposive sample was selected that consisted of (258) clients divided into two groups, a case group (172) clients with thyroid cancer and a control group (86) clients without goiter and thyroid cancer. Results: According to the age, the highest percentage was in the age group (50-59 years), constituted (%33.7) for the case group. The majority of the case group are female who were accounted (77.9%); female to male ratio 4:1. The incidence of differentiated thyroid carcinoma according to histopathology was increased for women compared with men especially papillary thyroid carcinoma. Conclusion: The statistical analysis shows that there are significant relationships in previous history for goiter, family history for thyroid cancer, and exposure to radio-active iodine items with respect to the risk factors of thyroid cancer.